Soil Conservation Benefits of Ecological Programs Promote Sustainable Restoration - Renjie Zong; Nufang Fang; Yi Zeng; Xixi Lu; Zhen Wang; Wei Dai; Zhihua Shi (Earth's Future)
Abstract Ecological restoration efforts in less developed regions confront a sustainability challenge due to the undervaluation of their substantive benefits. Soil conservation, as a crucial ecosystem service supporting both ecological and socioeconomic systems in less developed regions, is often overlooked in estimating the benefits of restoration efforts. We introduce a framework that integrates the multi‐model approach and scenario analysis on cloud computing platforms to capture the significance of soil conservation benefits by assessing the world's largest restoration programs from China. Our analysis reveals that these restoration programs, with a total investment of $133 billion, have prevented 7.29 ± 1.01 Pg of soil erosion, valued at $243.0 ± 25.9 billion from 2000 to 2019. Notably, two critical programs that synergize forest conservation, cropland conversion, and human well‐being in China's less developed regions account for approximately 85% of the soil conservation benefits. Our findings underscore that soil conservation benefits significantly enhance the substantive benefits and prioritization of restoration efforts in less developed regions, reinforcing the potential for global restoration efforts to contribute to a sustainable future.